Effect of live and artificial feeds on the growth and survival of Macrobrachium malcolmsonii (H. Milne Edwards) larvae and juveniles - Soundarapandian, P; Ravichandran, S; Kannupandi, T (Indian Journal of Fisheries, 2011)
Freshwater prawn, Macrobrachium malcolmsonii, is a potential species foraquaculture. Larvae of M. malcolmsonii were reared in synthetic brackishwaterusing commercial salts. Live and artificial feeds were provided, either individuallyor in combination. Survival was significantly higher when Artemia wascombined with other feeds. Weight gain of the juveniles fed with adult Artemia(8.41 g), earthworm (4.90 g) and oyster (4.54 g) was better than those fed withartificial feed I (3.18 g) and II (3.86). Among the five feeds tested Artemia wasbest for M. malcolmsonii larvae and juveniles.